2008
DOI: 10.1073/pnas.0710868105
|View full text |Cite
|
Sign up to set email alerts
|

Domain requirement of moenomycin binding to bifunctional transglycosylases and development of high-throughput discovery of antibiotics

Abstract: Moenomycin inhibits bacterial growth by blocking the transglycosylase activity of class A penicillin-binding proteins (PBPs), which are key enzymes in bacterial cell wall synthesis. We compared the binding affinities of moenomycin A with various truncated PBPs by using surface plasmon resonance analysis and found that the transmembrane domain is important for moenomycin binding. Full-length class A PBPs from 16 bacterial species were produced, and their binding activities showed a correlation with the antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 29 publications
0
42
2
Order By: Relevance
“…We have previously observed that the binding affinity of moenomycin to E. coli PBP1b is TM domain dependent (9). However, no direct interaction between moenomycin and the TM helix was observed in our crystal structure.…”
Section: Resultscontrasting
confidence: 43%
See 3 more Smart Citations
“…We have previously observed that the binding affinity of moenomycin to E. coli PBP1b is TM domain dependent (9). However, no direct interaction between moenomycin and the TM helix was observed in our crystal structure.…”
Section: Resultscontrasting
confidence: 43%
“…2 B and C). The resemblance between our structure and SaPBP2 may explain the observation that transglycosylases from E. coli and S. aureus share comparable binding affinity to moenomycin (9). In addition, the interacting residues of the TG domain around the E ring, the F ring, the phosphate group, and the carboxylate group of moenomycin are more conserved than the interacting residues with the remaining parts ( Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…78 This theory is supported by the fact that the transmembrane portion of PBPs is necessary for moenomycin binding. 80 …”
Section: Moenomycinsmentioning
confidence: 99%